2019
DOI: 10.1111/vox.12785
|View full text |Cite
|
Sign up to set email alerts
|

One‐unit compared to two‐unit platelet transfusions for adult oncology outpatients

Abstract: Background and Objectives Platelet dosing has been studied in adult oncology inpatients, but there is almost no published evidence to guide platelet dosing for adult outpatients. We evaluated transfusion indices after 1 unit and 2 unit apheresis platelet transfusions at our hospital to determine whether a benefit to 2‐unit transfusions could be detected. Materials and Methods A retrospective chart review was conducted of all adult oncology patients who received an outpatient platelet transfusion over a 16‐mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Studies of transfusion requirements in acute leukaemia have focused only on one category of blood product and used different endpoints that not allows robust comparison between studies. Criteria reported were, regarding platelet usage, bleeding control or corrected implement count, 1–3,7 or prophylactic or therapeutic strategy, 8,9 and for the RBCs transfusion mainly haemoglobin levels 10–12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of transfusion requirements in acute leukaemia have focused only on one category of blood product and used different endpoints that not allows robust comparison between studies. Criteria reported were, regarding platelet usage, bleeding control or corrected implement count, 1–3,7 or prophylactic or therapeutic strategy, 8,9 and for the RBCs transfusion mainly haemoglobin levels 10–12 …”
Section: Discussionmentioning
confidence: 99%
“…reported were, regarding platelet usage, bleeding control or corrected implement count, [1][2][3]7 or prophylactic or therapeutic strategy, 8,9 and for the RBCs transfusion mainly haemoglobin levels. [10][11][12] We report blood product requirements during chemotherapy-induced aplasia in a large homogeneous cohort of 395 patients. On average, 2 RBCs and 2-3 PCs were transfused per week.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, hospitals have implemented PBM programs to advance restrictive transfusion practices with a view to improve patient outcomes, reduce costs, and conserve blood for transfusion. [40][41][42] Hospitals have implemented PBM programs, and PACS is a part of the PBM initiatives. The peak of the PACS was in 2008 and in general follows the decreasing trend concomitant with decrease in RBC transfusions overall and is concurrent with an increase in adoption of PBM programs.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence validating the improved patient safety afforded by PBM programs, blood conservation techniques (eg, PACS, presurgical hemostasis management, and enhanced and noninvasive surgical techniques) and adherence to transfusion guidelines. As a result, hospitals have implemented PBM programs to advance restrictive transfusion practices with a view to improve patient outcomes, reduce costs, and conserve blood for transfusion 40‐42 . Hospitals have implemented PBM programs, and PACS is a part of the PBM initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 One (vs. 2) apheresed unit transfusion is preferred as 2 units do not increase time between transfusions or platelet count at time of next transfusion due to short-lived effect on the platelet count. 31 Although previous reports suggest the role of antifibrinolytic agents in patients with severe persistent thrombocytopenia, 32 a recent RCT that included MDS patients showed that prophylactic treatment with tranexamic acid did not significantly reduce bleeding in patients receiving therapy. 33 However, the trial did not specifically address patients who are alloimmunized to donor platelets and do not have severe and refractory thrombocytopenia.…”
Section: Transfusion Support Red Blood Cellsmentioning
confidence: 99%